Pharmacological aspects of Borago officinalis (Borage): A review article - Ruaa Mohammed Ibrahim; Dhuha Abdul Saheb Alshammaa (College of Pharmacy University of Baghdad, 2023)
Abstract: Borago officinalis is highly interesting amongst nutritional and medical source relate to its high composition of some useful phytochemical compound. It is great plants with bright blue star-shaped flowers present in most world regions and usually known as borage. The Borago phytochemical analysis showed the presence of alkaloids, tannins, flavonoids, phenolic acids, essential oil, vitamins and others. Borage is cultivated all over the world and used in traditional medicine as a demulcent, diuretic, emollient, tonic, expectorant, for the treatment of coughs, inflammation and swelling, and other diseases. In herbal medicine, Borage seed oil (BSO) has been utilized for many progressive illnesses as a treatment agent. The BSO compounds include p-simen-8-L, ?-caryophyllene, sesquiterpenes, monoterpenes, alpha-linoleic, gammalinoleic and linoleic acid. BSO is famed to be the richest vegetable origin of gamma (?)-linoleic acid (GLA). Borage officinalis possess different pharmacological properties including antinociceptive, antioxidant, radioprotective, memory improving, hepatoprotective, antinflammatory, and analgesic effects.